Autumn of the moguls my misadventures with the titans, poseurs, and money guys who mastered and messed up big media - Wolff, Michael 1953- (New York, NY HarperBusiness, 2003)
A former media entrepreneur, Wolff has had a ringside seat as the conglomeratized worlds of newspapers, magazines, television, radio, and the Internet have taken often bewildering turns. In this book, Wolff explains it all, taking on the great (and not-so-great) characters of the age, including AOL Time Warner's Gerald Levin, Steve Case, Bob Pittman, and Walter Isaacson; New York Times publisher Arthur Sulzberger Jr.; News Corp.'s Rupert Murdoch; Viacom's Sumner Redstone and Mel Karmazin; media empress Martha Stewart; would-be media empress Tina Brown; legendary kahuna Barry Diller; media-mogul-turned-New-York-City mayor Michael Bloomberg; and Disney czar Michael Eisner. Also scrutinized is an outrageous cast of self-proclaimed creative geniuses, short-sighted (and often short) financiers, and shameless politicians who attempt and frequently succeed in manipulating the media.--From publisher description
Includes index.
KAL-3344, donated by Prof. Thomas David F. Chavez.
Keywords: Wolff, Michael -- 1953-.; Mass media -- Biography; Mass media